A abordagem da variação linguística nas competências e habilidades da BNCC do ensino médio - Paula, Maria Izabel Nunes de (2023)
This dissertation deals with the treatment of linguistic variation in the National Common Curricular Base for Secondary Education. The main objective is to analyze the skills and abilities that explain linguistic variation in the High School BNCC, with a view to identifying and understanding the adopted language perspective. This objective is segmented into others considered specific, such as: mapping skills and abilities focused on linguistic variation, which are present in the BNCC of High School, in order to investigate the extent to which these skills match the theory; understand, by looking at the Portuguese Language skills and abilities at BNCC in High School, the perspective of the present language; and identify the approach to linguistic variation as an object of knowledge in the language practices of the PL curricular component at BNCC in High School. As for the theoretical basis, it is anchored in the assumptions of Labov (2008), Bortoni-Ricardo (2004 and 2005), Alkmim (2012), Geraldi (2012), Beline (2021), also dialoging with authors such as Travaglia (2009) , Bakhtin (2004) Chomsky (2005) and Volochinov (2018). To fulfill the proposed objectives, an investigation was carried out with a qualitative approach, with an interpretative basis, of a documentary type, based on the assumptions of Sociolinguistics, in particular, Educational Sociolinguistics, discussing concepts such as language heterogeneity, linguistic variation and teaching. The research takes as its corpus the BNCC version (Brazil, 2018), more precisely, the specific part related to the area of ​​Languages ​​and its technologies and the Portuguese language curricular component in high school. Through the mapping carried out in the research corpus, it was observed that due to the considerable number of specific skills and abilities in the area of ​​Languages ​​and their Technologies and the Portuguese Language curricular component, the number of those that explain the notion of language in use is irrelevant. However, carrying out a more detailed analysis of the terms of other skills that do not make this notion explicit, it was observed that there are possibilities for the teacher to explore linguistic variations in their context of use. By looking at the Portuguese Language skills and abilities in the National Common Curricular Base for High School, described in this analysis, it was possible to infer that the language perspective present in the document is socio-interactionist.